Analisis Sintaks dan Sistem Sosial pada Model Project-Based Learning Berbasis Adversity Quotient dalam Pembelajaran Kewirausahaan - Rosida, Vivi; Bakhtiar, Muh. Ilham; Haruna, Hasisa; Nasrul, Nasrul (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2025)
This study aims to analyze the syntax and social system in the implementation of the Project-Based Learning (PjBL) model integrated with the Adversity Quotient (AQ) in entrepreneurship learning for students at STKIP Andi Matappa. The research employs a descriptive qualitative approach with a case study design, involving students and lecturers of the Entrepreneurship course as research subjects. Data were collected through participatory observation, in-depth interviews, and document analysis, and then analyzed using the Miles and Huberman model through the processes of data reduction, data display, and conclusion drawing. The results show that the PjBL-AQ syntax is systematically implemented through six phases, namely identifying essential questions, designing project planning, conducting investigations, monitoring and mentoring, testing project outcomes, and evaluation and reflection. Each phase demonstrates AQ indicators (Control, Ownership, Origin, Reach, and Endurance/CO2RE), which play a role in developing students’ entrepreneurial readiness. Furthermore, the emerging social system indicates a collaborative relationship among lecturers, students, and business partners. Lecturers act as active facilitators, students exhibit strong independence and teamwork, while collaboration with entrepreneurs strengthens students’ authentic learning experiences. The findings confirm that integrating PjBL with AQ is effective in developing students’ resilience, creativity, responsibility, and entrepreneurial readiness through contextual and applicable learning experiences. This study recommends strengthening AQ evaluation instruments and expanding external partnerships to enhance the sustainability of the model’s implementation.